2019
DOI: 10.1002/mcf2.10102
|View full text |Cite
|
Sign up to set email alerts
|

Recreational Angler Attitudes and Perceptions Regarding the Use of Descending Devices in Southeast Reef Fish Fisheries

Abstract: Reducing discard mortality in recreational fisheries remains an important component of stock rebuilding for many reef fish species. Discard mortality for these species can be high due in part to barotrauma injury sustained during capture coupled with high catch rates, but recent advances in fish descending devices can mitigate some of these declines. Despite high survival rates with rapid recompression strategies, recreational angler opinions and perceived effectiveness of the devices are relatively unknown. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 20 publications
0
15
0
Order By: Relevance
“…It is clear that compliance with the requirement to carry a descender device does not necessarily translate to actual use. Education and outreach, including demonstrations and presentations detailing findings such as those of the present study, are crucial to increasing the use of descender devices (Crandall et al 2018;Curtis et al 2019;Runde 2019). Vecchio et al (2020) surveyed 801 boat parties on the east coast of Florida during recent recreational Red Snapper seasons and found that only 1.5% reported using descender devices, although venting is used more commonly (Scyphers et al 2013).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…It is clear that compliance with the requirement to carry a descender device does not necessarily translate to actual use. Education and outreach, including demonstrations and presentations detailing findings such as those of the present study, are crucial to increasing the use of descender devices (Crandall et al 2018;Curtis et al 2019;Runde 2019). Vecchio et al (2020) surveyed 801 boat parties on the east coast of Florida during recent recreational Red Snapper seasons and found that only 1.5% reported using descender devices, although venting is used more commonly (Scyphers et al 2013).…”
Section: Discussionmentioning
confidence: 86%
“…Vecchio et al (2020) surveyed 801 boat parties on the east coast of Florida during recent recreational Red Snapper seasons and found that only 1.5% reported using descender devices, although venting is used more commonly (Scyphers et al 2013). However, Curtis et al (2019) determined that once introduced to descender devices, 76% of anglers reported that they would continue using them. This information has been taken into account for the most recent stock assessment in the SEUSA (SEDAR 2021).…”
Section: Discussionmentioning
confidence: 99%
“…2015; Curtis et al. 2019). Additionally, we were unable to survey anglers from all Gulf of Maine states (i.e., NH) as well as nonlicensed anglers who can legally fish on for‐hire platforms, like charter boats and party boats.…”
Section: Discussionmentioning
confidence: 99%
“…2013; Curtis et al. 2019). Moreover, even if they are likely to voluntarily adopt such practices, anglers use a variety of channels (e.g., online and print media; word of mouth) to receive angling‐related information, which complicates effective outreach efforts (e.g., Nguyen et al.…”
mentioning
confidence: 99%
“…As a result of this research, descender devices are required gear onboard any vessel fishing for or possessing reef species in the southeastern United States (SAFMC 2020). However, while anglers are generally receptive to incorporating descending into their normal fishing routines after appropriate outreach and education (Crandall et al 2018;Bellquist et al 2019;Curtis et al 2019;Runde 2019), usage rates remain low in the southeastern U.S. Atlantic (Vecchio et al 2020).…”
mentioning
confidence: 99%